Assessing Fiscal Risks in Bangladesh - Medina, Leandro (IMF Working Papers; Working Paper, 2015)
This paper identifies, quantifies, and assesses fiscal risks in Bangladesh. By performing sensitivity analysis and using stochastic simulations, it measures risks arising from shocks to GDP growth, the exchange rate, commodity prices, and interest rates. It also analyzes specific fiscal and institutional risks, such as those related to the pension system, the issuance of guarantees, the state-owned commercial banks, and the external borrowing and debt management strategy. The paper finds that fiscal aggregates are particularly sensitive to shocks to commodity prices and exchange rates. Other factors that could affect fiscal aggregates are the unfunded pension system and the limited institutional capacity.